LITERASI VISUAL MEDIA EDUKASI POSTER TERKAIT COVID-19 PADA SISWA SMA DI KOTA PADANG - Ullya Mega Wahyuni; Jefril Rahmadoni; Afriyanti Dwi Kartika; Adi Arga Arifnur; Husnil Kamil; Meza Silvana; Ricky Akbar; Wahyudi Wahyudi (Jurnal Hilirisasi IPTEKS, 2021)
Officially the World Health Organization (WHO) has determined that COVID-19 is a pandemic, and the Indonesian government has also declared the Corona outbreak a national disaster. To be able activities during a pandemic, we must carry out Communication, Information, and Education (IEC) to the public regarding COVID-19. IEC can be done by using posters as a communication medium. Socialization of education media is aim at high school students in the city of Padang. The purpose of this activity is to provide training to high school students in the city of Padang so that the knowledge provided can be used by making educational posters and share information related to COVID-19 to the public through social media as of concern for students to reduce the spread Coronavirus. This activity involved students from four schools in Padang, namely SMAN 7, SMAN 11, SMA Pertiwi 2, and SMA Don Bosco Padang. The method of implementing activities consists of three stages, namely preparation, implementation, and evaluation. During the activity, participants were very enthusiastic about participating in the activity until the final stage. This activity's target achievement was 90% seen from the participants who collected educational posters during the training. Meanwhile, the participants' visual literacy ability was 85%, assessed from participants' understanding in conveying visual messages into educational posters. To motivate participants to stay enthusiastic study during pandemics, the best posters were selected from the activity participants.